In-hospital stroke protocol outcomes before and after the implementation of neurological assessments by telemedicine: an observational case–control study - Massaud, Rodrigo Meirelles; Accorsi, Tarso Augusto Duenhas; Massant, Cristina Gonçalves; Silva, Gisele Sampaio; de Carvalho Leite, Anna Verena; Franken, Marcelo; Moreira, Flavio Tocci; Köhler, Karen Francine; De Amicis Lima, Karine; Morbeck, Renata Albaladejo; Pedrotti, Carlos Henrique Sartorato (Frontiers in Neurology, 2024)
Purpose Stroke is the second leading cause of global adult mortality and the primary cause of disability. A rapid assessment by a neurologist for general and reperfusion treatments in ischemic strokes is linked to decreased mortality and disability. Telestroke assessment is a strategy that allows for neurological consultations with experienced professionals, even in remote emergency contexts. No randomized studies have compared face-to-face neurological care outcomes with telestroke care. Whether neurologists in an institution achieve better results remotely than in person is also unknown. This study aimed to compare mortality and other outcomes commonly measured in stroke protocols for stroke patients assessed by a neurologist via face-to-face evaluations and telestroke assessment. Methods Observational single-center retrospective study from August/2009 to February/2022, enrolling 2,689 patients with ischemic stroke, subarachnoid hemorrhage, and intracerebral hemorrhage. Group 1 (G1) comprised 2,437 patients with in-person neurological assessments, and Telemedicine Group 2 (G2) included 252 patients. Results The in-person group had higher admission NIHSS scores (G1, 3 (0; 36) vs. G2, 2 (0; 26), p < 0.001). The door-to-groin puncture time was lower in the in-person group than in the telestroke group (G1, 103 (42; 310) vs. G2, 151 (109; 340), p < 0.001). The telestroke group showed superior metrics for door-to-imaging time, symptomatic hemorrhagic transformation rate in ischemic stroke patients treated with intravenous thrombolysis, hospital stay duration, higher rates of intravenous thrombolysis and mechanical thrombectomy, and lower mortality. Symptomatic hemorrhagic transformation rate was smaller in the group evaluated via telestroke (G1, 5.1% vs. G2, 1.1%, p = 0.016). Intravenous thrombolysis and mechanical thrombectomy rates were significantly higher in telestroke group: (G1, 8.6% vs. G2, 18.2%, p < 0.001 and G1, 5.1% vs. G2, 10.4%, p = 0.002, respectively). Mortality was lower in the telestroke group than in the in-person group (G1, 11.1% vs. G2, 6.7%, p = 0.001). The percentage of patients with an mRS score of 0–2 at discharge was similar in both groups when adjusting for NIHSS score and age. Conclusion The same neurological emergency team may assess stroke patients in-person or by telemedicine, with excellent outcome metrics. This study reaffirms telestroke as a safe tool in acute stroke care.